А study of the influence of the transverse dimensions of beech of strips on the form of stability of furniture board - Podibka, T.I.; Kiyko, O.A. (Forestry, Forest, Paper and Woodworking Industry, 2019)
It has been established that the wood of hardwood species in a massive form, in particular defect-free pieces of common beech wood (Fagus sylvatica L.) is a suitable resource for the manufacture of furniture panels, since glued structures with the correct selection of transverse dimensions of the rails have the acceptance of internal stresses, which is reflected in the form of panel glued structures. The regularities of the influence of the thickness and width of the slats on the dimensional stability of furniture boards made of hardwood species, in particular common beech (Fagus sylvatica L.), were obtained. Based on the results of experimental studies, an adequate regression equation of the second order was obtained, using the B-plan, to determine the arrow of the deflection of glued shields, depending on the thickness and width of the blanks. It was found that the minimum deviation Smin = 0.067 mm, taken as an absolute value, can be obtained by fixing the dimensional parameters of the slats of the furniture board: the thickness of the slats from common beech (Fagus sylvatica L.) Bthickness (x1) = 32 mm; width of the rail made of common beech (Fagus sylvatica L.) (tangential) Bwidth (x2) = 36 mm. The influence of variable factors on dimensional stability has been determined, in particular, it should be noted that variable factors affect differently: thickness – inversely proportional, i.e. ensures dimensional stability of the structure, width – directly proportional, i.e. increases the deflection beam with increasing width. The second factor width (x2) – the width of the slats – has the greatest effect on the dimensional stability of furniture boards made of hardwood species, in particular common beech (Fagus sylvatica L.) with alternate stacking. The influence of the first factor Bthickness (x1) on dimensional stability compared to the second factor width (x2) is 1.32 times smaller. It was established that the deviations from flatness along the deflection arrow for most samples of experimental slabs meet the requirements of regulatory documents, except for one where 84 mm wide rails were used. When laying a rail with a thickness of 16 mm, the width of the rail cannot be wider than 70 mm, since the value of the deflection arrow from flatness will be greater than the standard value, i.e. for a width of furniture boards up to 500 mm, it is 0.4 mm (according to the 13th degree of accuracy). Practical recommendations for the production of furniture boards from hardwood species, in particular common beech (Fagus sylvatica L.): it is necessary to use a ratio of sides in the cross section of the rails of 1:3, i.e. the width of the rails for a furniture board thickness of 16 mm should be 40-50 mm, with with a thickness of 24 mm, it should be 70-75 mm, with a thickness of 32 mm, it should be 85-90 mm, since a decrease in the width of the workpiece leads to an increase in cost (the number of operations and glue consumption increases), and an increase in width leads to a deterioration of dimensional stability; selection of rails by width and thickness with alternating laying, giving preference to radial ones, application of glue to the edges of the rails with a consumption of 200-220 g/m2, gluing in wicks (mode parameters: temperature – 90-92 ºС, exposure time – 25-30 min , pressure – 0.9-1.5 MPa), technological aging (humidity – 50±5%, temperature 20±2 ºС) for 6-9 hours.